Cancer: a family at risk - Woźniak, Katarzyna; Iżycki, Dariusz (Menopause Review/Przegląd Menopauzalny, 2014)
The diagnosis of cancer is a family experience that changes the lives of all its members, bringing an immense amount of stress and many challenging situations. The daily routine, common activities and distribution of duties all have to change. Family members follow the phases of the disease, very often suffering comparable or greater distress than the patient. They use various coping methods which aim at helping both the sick relative and themselves. These methods, together with emotional responses, change over time according to the phase of the disease. Cancer puts the family at risk since it imposes an alternation in the relations among family members. It affects the couple’s relationship, their sex life, and it can also be a cause of major trauma among their children and adolescents. The diagnosis of cancer brings also individual risks for the family members in terms of psychological and physical health impairment. Family caregivers often feel overloaded with the additional obligations and roles they have to pick up. They find it increasingly burdening to care full-time for the household and provide emotional support for the patient. The family’s problems and the way family members regard the disease may be also a result of the family system they are in. This article describes the nature of caregiving to a patient with cancer and the biggest concerns for the family.